Hypercalcemia of Malignancy: Clinical Characteristics and Treatment Outcome - Wijaya, Indra; Oehadian, Amaylia; Sumantri, Rachmat (Faculty of Medicine, Universitas Padjadjaran, 2014)
Hypercalcemia is one of the most common paraneoplastic syndromes in hospitalized malignancy patients. The aim of this study was to determine the clinical characteristics and treatment outcome in hypercalcemia of malignancy. This was a study using medical records of patients with malignancy hospitalized in the Departement of Internal Medicine, Dr. Hasan Sadikin Hospital Bandung between December 2008 and March 2011. Statistical analysis was performed by Wilcoxon and Mann-Whitney tests. There were 40 patients with hypercalcemia of malignancy, consisted of 22 hematologic malignancies and 18 solid tumors. Disturbance of consiousness were found in 4, dehydration in 18, constipation in 6, and nausea and vomiting in 6 subjects. In 16 subjects, no symptoms were found. All subjects received rehydration with normal saline. Bisphosphonate was given in 26 subjects. The difference of decreasing ion calcium level, between the groups who were treated with or without bisphosphonate was 0.59 (0.01–1.17) mg/dL, p=0.0001. In conclusion, hematologic and solid tumors are found in about the same proportion in hypercalcemia associated malignancy. Treatment either with or without bisphosphonate shows good results. [MKB. 2014;46(2):111–17]Key words: Bisphosphonate, hypercalcemia of malignancy, rehydrationHiperkalsemia pada Keganasan: Karakteristik Klinik dan Luaran TerapiHiperkalsemia merupakan salah satu sindrom paraneoplasma yang sering ditemukan pada pasien keganasan. Tujuan penelitian ini untuk mengetahui karakteristik klinis dan respons terapi penderita dengan hiperkalsemia pada keganasan. Penelitian ini menggunakan data rekam medis pasien yang dirawat di Departemen Penyakit Dalam Rumah Sakit Dr. Hasan Sadikin Bandung periode Desember 2008–Maret 2011. Analisis statistik menggunakan Uji Wilcoxon. Dari 40 penderita dengan hiperkalsemia pada keganasan, didapatkan 22 keganasan hematologi dan 18 tumor padat. Gejala klinis yang ditemukan adalah gangguan kesadaran pada 4 subjek, dehidrasi pada 18 subjek, konstipasi pada 6 subjek, mual dan muntah pada 6 subjek. Pada 16 subjek tidak ditemukan gejala. Semua subjek mendapatkan rehidrasi dengan NaCl 0,9%. Dua puluh enam subjek mendapat terapi bisfosfonat. Perbedaan penurunan kadar kalsium ion antara kelompok yang mendapatkan bisfosfonat dan tidak adalah 0,59 (0,01–1,17) mg/dL, p=0,0001. Simpulan, proporsi keganasan penyebab hiperkalsemia hampir sama antara keganasan hematologi dan tumor padat. Terapi rehidrasi dengan NaCl 0,9% tanpa atau disertai bisfosfonat memberikan hasil yang baik. [MKB. 2014;46(2):111–17]Kata kunci: Bisfosfonat, hiperkalsemia pada keganasan, rehidrasi DOI: 10.15395/mkb.v46n2.283